2017
DOI: 10.1007/s10517-017-3822-y
|View full text |Cite
|
Sign up to set email alerts
|

Study of Endothelial Protective Activity of Phenol-Derived Thrombin and Arginase-2 Inhibitors KUD-259 and KUD-974

Abstract: We performed correction of endothelial dysfunction with phenol derivatives KUD-259 and KUD-974 containing heteroatomic and heterocyclic structures. Pharmacological activity of KUD-259 and KUD-974 surpassed that of L-norvaline, a non-selective arginase inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Previously, we developed and studied acute toxic effects [28,29] and the pharmacological activity of a number of phenolic compounds that are inhibitors of arginase-2 and thrombin. The pharmacological activity of the developed compounds is shown in our laboratory on various experimental models of endothelial dysfunction [30,31]. The leader -methyl ether (2 -((1hydroxy-naphthalen-2-yl) thio) acetyl) -D-proline compound was selected under the laboratory code KUD-975.…”
Section: Results and Dissectionmentioning
confidence: 99%
“…Previously, we developed and studied acute toxic effects [28,29] and the pharmacological activity of a number of phenolic compounds that are inhibitors of arginase-2 and thrombin. The pharmacological activity of the developed compounds is shown in our laboratory on various experimental models of endothelial dysfunction [30,31]. The leader -methyl ether (2 -((1hydroxy-naphthalen-2-yl) thio) acetyl) -D-proline compound was selected under the laboratory code KUD-975.…”
Section: Results and Dissectionmentioning
confidence: 99%
“…The preclinical studies of the selective arginase II inhibitor ZB49-0010 in various pathology models showed its pronounced endothelial protective properties that are superior to those for the non-selective inhibitor of L-norvaline Nguyen et al 2016;Severinova et al 2019). The literature contains data on the endothelial protective properties of arginase II selective inhibitors KUD-259 and KUD-974 on the functional state of vascular endothelium (Pokrovskii et al 2017); however, to date, studies of their effectiveness have not been conducted in experimental preeclampsia yet. Thus, it becomes obvious that short-lived erythropoietin derivatives that do not have an erythropoietic effect and selective arginase II inhibitors can serve as another promising area for searching for new drugs to prevent and correct preeclampsia.…”
Section: Resultsmentioning
confidence: 99%
“…Another promising group of drugs for the treatment of hypertensive conditions in pregnant women is arginase inhibitors (Nguyen et al 2016;Severinova et al 2019). At the same time, arginase II inhibitors as being more selective are of particular interest (Pokrovskii et al 2017;Gureev et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Now numerous promising molecules of drugs are being studied with a high potency to have cardioprotective, antiischemic and antiarrhythmic properties, to correct endothelial dysfunction in order to normalize regulation of vascular pressure and microcirculatory blood flow (Blinova et al 2016, Vasilkina et al 2016, Shakhno et al 2018, Pokrovskii et al 2017. Among the substances of the kinds, our attention was drawn to salts of 2-aminoethanesulfonic acid containing magnesium and dimethylphenylacetamide as a base.…”
Section: Introductionmentioning
confidence: 99%